2015
DOI: 10.4103/0253-7176.150817
|View full text |Cite
|
Sign up to set email alerts
|

Apraxias in Neurodegenerative Dementias

Abstract: Background:Apraxia is a state of inability to carry out a learned motor act in the absence of motor, sensory or cerebellar defect on command processed through the Praxis circuit. Breakdown in default networking is one of the early dysfunction in cortical dementias and result in perplexity, awkwardness, omission, substitution errors, toying behavior and unrecognizable gestures in response to command with voluntary reflex dissociation where, when unobserved patient will carry out reflex movements normally. Aware… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 13 publications
0
21
0
1
Order By: Relevance
“…Disruptions in praxis can hinder a variety of basic and complex skills, including volitional movements of the eyelids, mouth, and tongue, speech production, the ability to mime practical movements (like lighting a match or brushing one's teeth), and gait. Dyspraxias, including gait dyspraxias, are often observed in people with dementia in both the general population and in individuals with DS (Chandra et al, 2015; Dalton and Fedor, 1998). …”
Section: Gait Dyspraxia In Dementiamentioning
confidence: 99%
“…Disruptions in praxis can hinder a variety of basic and complex skills, including volitional movements of the eyelids, mouth, and tongue, speech production, the ability to mime practical movements (like lighting a match or brushing one's teeth), and gait. Dyspraxias, including gait dyspraxias, are often observed in people with dementia in both the general population and in individuals with DS (Chandra et al, 2015; Dalton and Fedor, 1998). …”
Section: Gait Dyspraxia In Dementiamentioning
confidence: 99%
“…[8][9][10][11][12] In 1920, Lipeman studied 84 patients who suffered strokes and discovered that, in addition to aphasia, the patients also had impairments of motor skills such as debilitated copying and imitative gestures. 13 Moreover, regarding more precise aspects of the diagnosis, CAMCOG has contributed towards evaluation of total praxis and its subitems through showing the relevance of some studies that have indicated that impairment of praxis abilities confirms that there is a risk of rapid evolution to severe cases of dementia. 10,14…”
Section: Introductionmentioning
confidence: 99%
“…IPT consists in copying two intersecting pentagons, and requires understanding, execution and visuospatial coordination. More specifically, IPT is aimed to evaluate constructional apraxia (CA), which is defined as the inability to draw two or three‐dimensional objects using single dimension lines . It has already been recognized as valuable screening tool to identify subjects with Alzheimer disease and to predict inability to perform pulmonary function tests correctly …”
Section: Introductionmentioning
confidence: 99%